A 2.5D computational method to simulate cylindrical fluidized beds. (17th February 2015) - Li, Tingwen; Benyahia, Sofiane; Dietiker, Jean-François; Musser, Jordan; Sun, Xin
Abstract: In this paper, the limitations of axisymmetric and Cartesian two-dimensional (2D) simulations of cylindrical gas–solid fluidized beds are discussed. A new method has been proposed to carry out pseudo-two-dimensional (2.5D) simulations of a cylindrical fluidized bed by appropriately combining the benefits of Cartesian 2D and axisymmetric assumptions. This is done by constructing a computational domain consisting of a central thin plate and two wedges. The proposed method was implemented in the open-source code MFIX and applied to the simulation of a lab-scale bubbling fluidized bed with necessary sensitivity study. After a careful grid study to ensure the numerical results are grid independent, detailed comparisons of the flow hydrodynamics were presented against axisymmetric and Cartesian 2D simulations. Furthermore, the 2.5D simulation results have been compared to the three-dimensional (3D) simulation for evaluation. This new approach yields better agreement with the 3D simulation results than with axisymmetric and Cartesian 2D simulations. Highlights: Limitations of axisymmetric and 2D simulations of fluidized beds are discussed. A 2.5D simulation of a cylindrical fluidized bed is proposed. Careful verification study has been conducted for both 2D and 3D simulations. The new model yields better agreement with the 3D simulation results.